Exploring destination sustainable development strategies: Triggers and levels of maturity - Francesca d'Angella; Samuele Maccioni; Manuela De Carlo (Sustainable Futures)
Sustainability is a key determinant of destination competitiveness. While most tourism destinations have embarked on the path toward sustainability, approaches, policies and outcomes vary widely. Despite the extensive literature on sustainability, few studies have examined the maturity level of sustainability strategies, the role of Destination Management Organizations (DMOs), and the key drivers of sustainable destination development. Our study addressed this gap through an empirical analysis of an Italian alpine region, using a mixed-method approach that integrated quantitative data with qualitative insights from interviews with DMO managers. We identified four main stages in sustainable destination development: awareness, agenda setting, action, and monitoring. We propose extending Mihalic's Triple-A model to include the “monitoring” stage. Our findings highlighted the pivotal role of DMOs as facilitators and underscore the influence of both external (regulations, societal expectations, environmental crises) and internal (leadership, dynamic sustainability capabilities, and sustainability as an identity marker) triggers in determining the maturity of sustainability strategies. These outcomes offer an up-to-the-moment perspective on the stages in sustainable development, with interesting implications for destination managers. Building on our research, future studies could explore these dynamics in different contexts to derive generalizable conclusions beyond specific local scenarios.